A Review of Solar Photovoltaic Concentrators - Mehrdad Khamooshi; Hana Salati; Fuat Egelioglu; Ali Hooshyar Faghiri; Judy Tarabishi; Saeed Babadi (International Journal of Photoenergy)
Throughout the recent centuries, the limits of using energy resources due to the cost and environmental issues became one of the scientists’ concerns. Because of the huge amount of energy received by the Earth from the sun, the application of photovoltaic solar cells has become popular in the world. The photovoltaic (PV) efficiency can be increased by several factors; concentrating photovoltaic (CPV) system is one of the important tools for efficiency improvement and enables for a reduction in the cell area requirement. The limits of the PV area can reduce the amount of absorbing irradiation; CPV systems can concentrate a large amount of sunlight into a smaller one by applying lenses or curved and flat mirrors. However, the additional costs on concentrating optics and cooling systems made CPV less common than nonconcentrated photovoltaic. This paper reviews the different types of PV concentrators, their performance with advantages and disadvantages, concentration ratio, acceptance angle, brief comparison between their efficiencies, and appropriate cooling system.